Intellectual property, partnerships and people - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
This article examines the legal arrangements with respect to the products resulting from public-private research partnerships, and the implications for small farmers in East Africa.